2023
DOI: 10.30657/pea.2023.29.51
|View full text |Cite
|
Sign up to set email alerts
|

Can smart city planning enhance the sustainable transition of the E.U. capitals? A project and strategy-based smart, sustainable performance analysis in the programming period 2014-2020

Mária Szalmáné Csete,
Tímea Baranyi

Abstract: Cities across the globe perceive their opportunities for digital transition pathways. This paper presents a project and strategy-based assessment of smart city ambitions in the light of sustainable urban development pathways in the European Union capitals considering the programming period 2014-2020. The purpose of the research is to understand better the smart city trends in Europe and identify any correlation between smart city and sustainability ambitions through the European capitals. The basis of the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Similarly, the declaration issued by the Second World Conference of the United Nations in 2021 confirmed that the transport sector is responsible for a quarter of greenhouse gases [14]. Therefore, transport is considered key to the promotion of lowemission development, with the reduction and neutrality of CO 2 emissions being one of the development goals of this sector [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the declaration issued by the Second World Conference of the United Nations in 2021 confirmed that the transport sector is responsible for a quarter of greenhouse gases [14]. Therefore, transport is considered key to the promotion of lowemission development, with the reduction and neutrality of CO 2 emissions being one of the development goals of this sector [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%